Assessment and Issues in the Taxation of Crypto Assets - Remeika, Robertas; Grigonis, Šarūnas (Vilnius University Open Series, 2024)
The paper provides a detailed assessment of the current tax treatment of crypto assets in Lithuania, the European Union and international law. It draws attention to and assesses the problematic aspects related to crypto tax regulation. The study starts by providing statistics on the development of the cryptocurrency market in Lithuania and discusses the current taxation model. The second part of the paper describes the current model of taxation of crypto-assets and presents problematic aspects of taxation of crypto-assets, such as the regulation of individual activity, the timing of taxation, and the extraction of cryptoassets. The third part of the paper describes the European Union law relating to the taxation of cryptoassets and discusses the guidelines of the Organisation for Economic Co-operation and Development. The growing popularity of crypto assets as a form of investment instrument has forced the state authorities to react: the State Tax Inspectorate of the Republic of Lithuania clearly states the criteria for taxation and the tax obligations, and the decision of the European Court of Justice puts cryptocurrencies on an equal footing with ordinary currencies, which are subject to the same taxes. The taxation of crypto-assets also raises some problematic aspects regarding the concept of individual activity and occasional crypto-transactions, the proper collection of data, and there are certain aspects that could lead to additional measures by the authorities at the Lithuanian or EU level.